The impact of perceived and measured threats in modifying children's active mobility behaviour - Zougheibe, Roula (Curtin University, 2023)
This study examined influences, either in the neighbourhood social environment in everyday life (i.e., measured and perceived safety) or threats during abnormal events (i.e., a health crisis) on primary school-aged children's outdoor active mobility behaviour, and their well-being. Based on extensive literature review, survey of parents and their children, and analytics, this work made several contributions to the body of knowledge. The findings have important implications for policy-making and future research.